Degradation of chlorpyrifos, cypermethrin and chlorothalonil pesticides in aqueous solution by FeGAC/H2O2 process - Affam, A.C. (Taylor and Francis Inc., 2016)
This study examined the degradation of pesticide aqueous solution containing chlorpyrifos, cypermethrin and chlorothalonil by the FeGAC/H2O2 process. Under the operating conditions (FeGAC 5Â g/L, H2O2 concentration 100Â mg/L and pH 3), chemical oxygen demand (COD) and total organic carbon removal were 96.2 and 79.2, respectively, and biodegradability (BOD5/COD ratio) increased from 0 to 0.40 after 60 min reaction. Complete degradation of chlorpyrifos, cypermethrin and chlorothalonil pesticides active ingredients occurred in 1Â min. Kinetic models such as pseudo-first-order, pseudo-second-order and intraparticle diffusion were evaluated. The Fourier transform infrared spectra (treated and untreated pesticide aqueous solutions) also indicated modification and/or degradation of the pesticide organic bonds. The study showed that FeGAC/H2O2 process can be used for the pretreatment of pesticide aqueous solution containing chlorpyrifos, cypermethrin and chlorothalonil before further treatment by biological process. Â© 2015 Balaban Desalination Publications. All rights reserved.